2007
DOI: 10.1080/09537100601078448
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume: Association with adverse neonatal outcome

Abstract: The aim of the study was to investigate on a possible association between maternal mean platelet volume (MPV) and oxygen-metabolic changes in pregnancies affected by altered maternal-fetal Doppler velocimetry. We considered the altered maternal-fetal Doppler velocimetry group (n = 57) pregnant women admitted to our Institution for a pregnancy complication associated to the event Pre-eclampsia (PE) and intrauterine growth retardation (IUGR), with altered Doppler velocimetry in the umbilical artery ( UA) (high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 17 publications
2
31
0
Order By: Relevance
“…In another study, Gioia et al . reported that MPV ≥ 10fL may be associated with adverse neonatal outcomes in women affected by abnormal uterine artery Doppler findings . The role of platelets in the pathophysiology of these studies was thrombosis secondary to inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…In another study, Gioia et al . reported that MPV ≥ 10fL may be associated with adverse neonatal outcomes in women affected by abnormal uterine artery Doppler findings . The role of platelets in the pathophysiology of these studies was thrombosis secondary to inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, Dundar et al showed that MPV increase during pregnancy, but it is more prominent in cases developing preeclampsia . Investigators described two different cutoff values, one was 8.5 fL (with a sensitivity of 78% and specificity of 86%) to determine risk of preeclampsia and the other was 10 fL (femtolitre) (with a sensitivity of 45% and specificity of 89.7%) to define the chance of unfavorable neonatal outcome (the necessity of severe oxygen support) . A combination of reduced platelet count and elevated MPV has a sensitivity of 90% and specificity of 83.3% in predicting preeclampsia .…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that MPV stands as a marker for prediction of PE development. Furthermore, Gioia et al proposed that a MPV cut-off value ≥ 10 fL may be considered as a further significant parameter that is able to predict unfavourable neonatal outcome in women affected by altered uterine artery Doppler velocimetry [37].…”
Section: Discussionmentioning
confidence: 99%